Differences in the Effects of Heavy Bag Thrust and Resistance Band Training On Arm Muscle Power in Lion Dojo Karate Athlete of the Year 2024 - Hutapea, Ricky Marcos; Manik, Syahputra; Dewi, Rahma; Purba, Pangondian Hotliber (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the Differences in the Effects of Heavy Bag Thrust and Resistance Band Training on Arm Muscle Power of Singa Dojo Karate Athletes in 2024. The research method used is the experimental method. The sampling technique used is purposive sampling. The number of athlete samples used was 16 people. This research was conducted at the Srigunting Complex, Block P. No. 50, Medan Sunggal District, Medan City, for 6 weeks with a training frequency of 3 (three) times a week. Statistical calculations using the t-test.The first hypothesis analysis uses pre-test and post-test data from the Heavy Bag Thrust exercise group on Arm muscle Power, where the t count is 4.705, the t table value is obtained with df = n - 1 (8 - 1 = 7) at a significant level of α = 0.05 is 1.894, thus t count> t table (4.705> 2.1318). Thus, it means that ho is rejected and ha is accepted, so it can be concluded that there is a significant effect of Heavy Bag Thrust exercise on the Arm muscle Power of the 2024 Singa Dojo Karate Athletes. The second hypothesis analysis uses pre-test and post-test data from the Resistance Band exercise group on Arm muscle Power, where the t count is 6.263, the t table value is obtained with df = n - 1 (8 - 1 = 7) at a significant level of α = 0.05 is 1.894, thus t count> t table (6.263> 2.1318). Thus it means that ho is rejected and ha is accepted, so it can be concluded that there is a significant effect of Resistance Band training on the arm muscle Power of Dojo Singa Karate Athletes in 2024.The third hypothesis analysis uses post-test and post-test data from the Heavy Bag Thrust and Resistance Band training group on Arm muscle Power, where the tcount is 68.10, the ttable value with dk = n - 1 (8 - 1 = 7) at the significant level α = 0.05 is 1.894, thus tcount > ttable (68.10 > 2.1318). This means that ho is rejected and ha is accepted, so it can be concluded that the Heavy Bag Thrust training variation has a significantly greater influence on the arm muscle power of the 2024 Singa Dojo karate athletes.